Transport Properties of Weyl Semimetal Mn3Sn - Miniotaité, Ugné (My University, 2022)
The antiferromagneticWeyl semimetalMn3Sn has recently been of great interest because of exotic transport behaviors it exhibits at room temperature, such as Planar Hall Effect (PHE), large AnomalousHall Effect (AHE) and negativemagnetoresistance (MR). These exotic behaviors, rarely found in antiferromagnets, have potential to be utilized in future spintronics devices. Mn3Sn compounds need to be stabilized in excess of Mn, which means that the actual composition is Mn3+δSn for δ ∈ [0.05,0.3]. Reports of the different exotic effects and other properties are therefore often attained from samples with varyingMn concentrations. In this thesis, we present extensive measurements of both magnetic and electronic transport properties of Mn3.13Sn for a wide temperature range, with the goal tomap all the transport properties ofMn3Sn for a single compound. All measurements have been conducted at the Jülich Centre for Neutron Science (JCNS) using the Quantum Design Physical Property Measurement System (PPMS) and Magnetic Property Measurement System (MPMS). We are able to identify three transition temperatures ofMn3.13Sn; Tf = 45K, Tt = 245K and TN = 410K. Below Tf , we confirm a weakly ferromagnetic phase with magnetic easy direction [0001]. AC susceptibility measurements also reveal a slight glassiness in this phase, consistent with the previous reports. Furthermore, MR measurements display competingWeak Localization and Anti-weak Localization effects belowTf . TN is identified as the Néel temperature above which the antiferromagnetic structure is destroyed. Above Tt , we clearly observe PHE, AHE as well as negative MR. Between Tf < T < Tt the Mn moments order in a spiral structure. In this temperature range both PHE, AHE and negative MR vanishes, consistent with earlier reports. We identify a six-fold anisotropy in magnetization confirming a triangular antiferromagnetic spin structure above Tt and observe the lowest-energy direction in the triangular configuration to be [11¯20]. This phase is also weakly ferromagnetic, and we find the easy direction to be in [11¯20] direction for low external magnetic field which shifts to [0001] at a high magnetic field. To further characterize the change in lowest-energy direction we suggest a more detailed study.
Keywords: Weyl Semimetal; Topological Materials; Planar Hall effect; Anomalous Hall effect; Mn3Sn; Weak Localization; Weak Anti-Localization; Chiral Anomaly